Noninsect Arthropods in Popular Music - Joseph R. Coelho (Insects, 2011)
The occurrence of noninsect arthropods in popular music was examined in order to explore human attitudes toward these species, especially as compared to insects. Crustaceans were the most commonly referenced taxonomic group in artist names, album titles and cover art, followed by spiders and scorpions. The surprising prevalence of crustaceans may be related to the palatability of many of the species. Spiders and scorpions were primarily used for shock value, as well as totemic qualities of strength and ferocity. Spiders were the most abundant group among song titles, perhaps because of their familiarity to the general public. Three noninsect arthropod album titles were found from the early 1970s, then none appear until 1990. Older albums are difficult to find unless they are quite popular, and the resurgence of albums coincides with the rise of the internet. After 1990, issuance of such albums increased approximately linearly. Giant and chimeric album covers were the most common of themes, indicating the use of these animals to inspire fear and surprise. The lyrics of select songs are presented to illustrate the diversity of sentiments present, from camp spookiness to edibility.